Analisis Harga Pokok Penjualan Produk Lampu Hias Pada Toko Sentosa Listrik di Kabupaten Toraja Utara - Ta'dung, Yohanis Lotong; Marewa, Jens Batara; Pasulu, Isak (UKI Toraja Press, 2022)
This study aims to determine the cost of goods sold for decorative lighting products at the Sentosa Electric Store in North Toraja Regency. The method used in this study is a quantitative method by identifying and collecting data in the form of numbers by describing the cost of goods sold by analyzing the research object. Data collection techniques and data analysis in this study were through literature study by studying literature such as books, research journals in the library and field studies by conducting observations and interviews with the formula for calculating the cost of goods sold. The results of this study indicate the cost of goods sold for decorative lighting products at the Sentosa Electric Store in North Toraja Regency, the cost of goods sold is Rp. 212,201,250. from the initial inventory of merchandise amounting to Rp. 82.890.000 plus purchases of Rp. 168.205,000 plus the purchase of transportation expenses of Rp. 24,000,000 so that a net purchase of Rp. 192,205,000 plus the cost of goods ready for sale amounted to Rp. 275,095. 000 then deducted the ending inventory of goods as of December 31, 2020 of Rp. 62,893,750 so that the total cost of goods sold is obtained.